Lab‐on‐paper surface‐enhanced Raman spectroscopy platform based on self‐assembled Au@Ag nanocube monolayer for on‐site detection of thiram in soil. (5th April 2019) - Lin, Xiang; Lin, Shuang; Liu, Yuanlan; Zhao, Haiyan; Liu, Benkang; Wang, Li
Abstract: A paper‐based surface‐enhanced Raman spectroscopy (SERS) substrate was prepared by assembling Au@Ag nanocubes onto a patterned paper with the assistance of a mask paper by liquid–liquid interface self‐assembly techniques. The paper‐based SERS substrate was glued to the glass slide to construct a novel lab‐on‐paper SERS platform. This paper‐based SERS sensor possesses a sample injecting zone together with a SERS detection zone in order that sample pretreatment and detection could be performed simultaneously. The SERS performance of this paper‐based sensor was investigated by using 4‐MBA as a probe molecule, and its enhancement factor as high as 0.56 × 10 5 could be obtained. Additionally, the SERS sensor demonstrated an excellent repeatability with the relative standard deviation for the variation from the spot‐to‐spot Raman intensity as low as 12.8%. Based on the superiority and functionality of this paper‐based SERS platform, sensitive SERS quantitative analysis of thiram in soil could be achieved, which suggests its significant application prospects for the measurement of pesticides in soil without any pretreatment. Abstract : A novel lab‐on‐paper SERS platform has been fabricated by assembling Au@Ag nanocubes (NCs) on patterned paper strips. The lab‐on‐paper SERS platform possesses a sample injecting zone together with a SERS detection zone in order that sample pretreatment and detection could be performed simultaneously. Therefore, on‐site detection of thiram in soil can be achieved, which suggests its significant application prospects for the measurement of pesticides in soil without any pretreatment.